Quality characteristics and volatile organic compound profiling of yellow mushrooms at different cap opening stages - Yang Wang; Wei Tong; Wen-Hui Zhang; Xiang-Bin Shi; Ying-Ying Yan; Xin-Ran Wu (Scientific Reports)
Abstract Yellow mushrooms (Floccularia luteovirens), which grow in high-altitude regions, are a component of traditional Tibetan medicine and have high nutritional value. In this study, the basic quality indices and volatile organic compounds (VOCs) of yellow mushrooms with different cap opening stages were determined. The volatile compounds (VOCs) were determined by headspace solid-phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS) technology. The results demonstrated that as the degree of cap opening increased, both the weight of individual mushrooms and their respiratory intensity exhibited an upward trend. However, there was no significant difference in firmness, and the color change was not obvious. A total of 99 VOCs were detected in yellow mushrooms. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) successfully differentiated the three groups of yellow mushrooms based on VOCs, indicating the presence of differentially volatile organic compounds (DVOCs) among the groups. Further, through orthogonal partial least squares discriminant analysis (OPLS-DA), hierarchical cluster analysis (HCA), venn diagram and K-means cluster analysis, the intergroup DVOCs and the specific high-abundance DVOCs were obtained. It revealed the differences in VOCs of yellow mushrooms with different cap opening stages, providing theoretical data for further exploring the quality changes of yellow mushrooms during storage and the traceability of their origin.